Malaysia Productivity Corporation (MPC) At Branch Kuching, Sarawak / Nurul Afifah Safari - Safari, Nurul Afifah (University Technology MARA Sarawak, 2018)
National Productivity Corporation was the formerly name for Malaysia Productivity Corporation. In 1962, National Productivity Corporation was established as a joint project between the United Nations Special Funds and the Federal Government, with the International Labour organisation acting as its executive (Malaysia Productivity Corporation). In 1966, the National Productivity Council (Incorporation) Act No. 19 was passed making the Centre an autonomous body. It was later amended as the National Productivity Council (Incorporation) (Amendment) Act A305 1975, to cater for expansion of the Centre's role. This act was subsequently amended as the National Productivity Centre (Incorporation) (Amendment) Act A801 1991. With the Act coming into effect on 1 December 1991, the National Productivity Council became the National Productivity Corporation.